In Search of Security: Migrant Workers' Understandings, Experiences and Expectations Regarding 'Social Protection' - TIMONEN, VIRPI; DOYLE, MARTHA (My University, 2009)
While both migration and welfare states are popular topics of research, the intersection between them is rarely studied. In this article, we present the findings of a study that explored migrant workers? conceptualisation of `social protection? and their relationship with the Irish welfare state. The main foci of analysis for the purposes of this article are the migrant workers? understandings, experiences and expectations regarding their social protection and the welfare state. While our findings hint at the presence of many migrant workers who are very poorly anchored into and even completely detached from the Irish welfare state, they also reveal complex and ambivalent attitudes towards component parts of the social protection system. While the findings presented here stem from a qualitative study in a single country, we hypothesise that similar patterns can be identified among the migrant populations in other, particularly liberal, welfare states.
PUBLISHED
Keywords: migrant; social protection; welfare state; work; liberal; security; migration; attitude